Introducing Village Culture as the Main Strategy in Achieving Successful Village SDGs - Prastyo, Redy Eko; Wisadirana , Darsono; Rozuli, Ahmad Imron; Hakim, Muhammad Lukman (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2025)
Preserving and advancing village culture is vital for sustainable development within communities. This study delves into its significance for SDGs, outlining challenges and opportunities in promoting awareness and value. Integrating village culture boosts community involvement, nurtures social ties, enhances economic prosperity, and protects the environment. Despite hurdles posed by modernization, globalization, and limited governance capabilities, collaborative actions and skill-building are key to surmounting obstacles. Reinforcing village culture empowers communities to bolster SDGs, champion local food systems, and enhance productivity, paving the way for a sustainable future rooted in local traditions and solutions.